Progress and impact of clinical phosphoproteomics on precision oncology - Lima, Nadia; Lee, Alex T. J.; Huang, Paul H. (Translational Cancer Research; Vol 6, Supplement 6 (August 29, 2017): Translational Cancer Research, 2017)
Advances in phosphoproteomic technologies have enabled a step-change in the ability to make precise measurements of global protein phosphorylation states within tumours, providing critical information on the activation status of key oncogenic pathways driving disease. As an ever increasing number of molecularly targeted drugs enact their effect through modulation of such pathways, translational phosphoproteomic studies represent an avenue for biomarker discovery that provides insight into the direct functional impact of drug treatment whilst uncovering previously unrecognised mechanisms of drug response and resistance. Array- and mass spectrometry (MS)-based techniques allow for the characterisation of hundreds to thousands of phosphorylation sites that in principle can be readily integrated with genomic and transcriptomic datasets to produce highly detailed molecular portraits of human cancers. However, in practice, the routine application of phosphoproteomics to clinically-derived material has been limited by factors relating to sample integrity, assay resolution and computational challenges. In this perspective, we highlight a number of recent studies that have applied phosphoproteomics to the analysis of tumour specimens and discuss their impact on our knowledge of dynamic pathway biology and response to targeted therapies. We provide examples of pioneering studies that have integrated phosphoproteomic data with genomic methods to demonstrate the utility of these approaches in identifying clinically important biology for applications in personalised medicine. Collectively, these studies suggest that the increasing use of phosphoproteomics in translational precision oncology holds the promise of contributing to practice-changing discoveries over the coming decade.